The Complaints, Type, and Severity of Stressful Events in Patients with Burning Mouth Syndrome Referring to Zahedan School of Dentistry, Iran - Nosratzehi T; Payandeh A; DehYadegari F (Dove Medical Press, 2020)
Tahereh Nosratzehi,1 Abolfazl Payandeh,2 Farnaz DehYadegari3 1Department of Oral Medicine, Oral and Dental Disease Research Center, Zahedan University of Medical Sciences, Zahedan, Iran; 2Department of Biostatistics and Epidemiology, Community Nursing Research Center, Zahedan University of Medical Sciences, Zahedan, Iran; 3Department of Oral Medicine, Zahedan University of Medical Sciences, Zahedan, IranCorrespondence: Tahereh NosratzehiDepartment of Oral Medicine, Oral and Dental Disease Research Center, Zahedan University of Medical Sciences, Zahedan, IranEmail taherehnosratzahi@yahoo.comIntroduction: Burning mouth syndrome (BMS) is a burning sensation in oral mucosa without visible lesions in clinical examinations. The present study aimed at comparing complaints, frequency, type, and severity of stressful events between patients with BMS and healthy individuals referred to Zahedan School of Dentistry, Zahedan, Iran.Materials and Methods: In the present study, 30 patients with BMS were matched with controls by age and gender after enrollment. The Holmes-Rahe questionnaire and the complaint registration form were used to compare the frequency of complaints, and the type and severity of stressful events between the groups. Data were analyzed by descriptive statistics, Chi-squared and t-tests.Results: The mean age of the subjects in the case and control groups was 40.13 ± 2.30 and 40.07 ± 2.31 years, respectively. The obtained results showed no statistically significant difference between the groups in terms of mean age and gender distribution (P> 0.05). The results of the Chi-squared test showed a significant difference in the frequency of complaints between the two groups (P< 0.001). The t-test results indicated that the average severity of complaints and the average severity of stressful events were significantly different between patients with BMS and controls (P< 0.001). The results of Chi-squared test revealed that the mean frequency of complaints (P< 0.001) and mean frequency of stressful events (P< 0.001) were significantly different between the two groups.Conclusions: Based on the study results, the frequency of complaints, and the type and severity of stressful events were significantly different between patients with BMS and healthy individuals referred to the clinic of Zahedan School of Dentistry.Keywords: burning mouth syndrome, stressful events, Holmes-Rahe